Certificação ambiental para associações recreativas e esportivas - Peralta, Aline Hanny (2017)
The need for minimalize the environmental impacts generated by buildings makes imminent the taking of concrete action to improve the quality of the built environments. In search, for the environmental quality, new management models were created, like the certifications for buildings environmental performance. Therefore, this study had as its objective the elaboration of a methodology for certification applied to operational sport and recreation associations, based on the existents environmental certifications. The analysis of the management system for energy, water and waste of one of these associations was also an objective of this study. For the certification elaboration criteria from LEED, AQUA, Casa Azul and PROCEL were selected and analyzed. These criteria were organized in predominant groups with the bigger relevance into the environmental management of the buildings, such as water management, energy management, solid waste management and social responsibility. In order to determine the punctuation for each criteria a research with a specific questionnaire was conducted with professionals realated to the subject. The Analytic Hierarchy Process (AHP) was used, which uses a pairwise comparison of the elements to determine the importance scale. As a result, the analysis of certification tends to be inadequate for use in sporting associations in operation. The AHP proved to be satisfactory as an instrument to support decision-making, since it allowed observing the hierarchy of the criteria of the certification against the opinions of professionals of each area. Regarding the association that was subject of this study, is possible to affirm that there is the possibility of improvement in environmental and social matters. In relation to the energy ambit of the association, the efforts to renew the lamps by the LED technology (Light Emitting Diod). However, the fact that the training pools are installed in open facilities, which implies the loss of energy in the form of heat mainly by evaporation. and consequently, in a greater consumption of diesel oil. With regard to water management at the club, it is worth noting the use of rainwater to supply irrigation demands. There is also the widespread use of water-saving devices such as automatic taps with aerators. However, the main negative point observed is the lack of water meters, since the main source of water is the sources and there is no way to measure the amount withdrawn in each use in the club. In the management of solid waste was verified the correct destination of the recyclable waste of the club, which allows the club to have a financial return from the sale of these materials. As a negative point the lack of segregation at source, resulting in a larger volume of waste sent to the landfill. With regard to the project studied, it is possible to attend a water and waste management with more contributions to environmental management of the club. There is a possibility of improvements in terms of energy management.